Probability Density Estimation Using Adaptive Activation Function Neurons - Fiori, S.; Bucciarelli, P.
In this paper we deal with the problem of approximating the probability density function of a signal by means of adaptive activation function neurons.We compare the proposed approach to the one based on a mixture of kernels and show through computer simulations that comparable results may be obtained with limited expense in computational efforts.
Keywords: ADAPTIVE ACTIVATION FUNCTION NEURONS; CUMULATIVE DISTRIBUTION FUNCTION; DIFERENTIAL ENTROPY; PROBABILITY DENSITY FUNCTION; STOCHASTIC GRADIENT